Perancangan Sistem Deteksi Plagiarisme Skripsi (Judul Dan Abstrak) Berbasis Matlab Menggunakan Algoritma Winnowing - Monalisa E. Rijoly; Windy Pramudita; Berny Pebo Tomasouw; Zeth Arthur Leleury (Tensor: Pure and Applied Mathematics Journal, 2021)
Plagiarism is an act of plagiarizing the work of others who will then acknowledge the work as one's own work without mentioning the source of the work. This research aims to create a plagiarism detection system using the winnowing algorithm in MATLAB to prevent plagiarism in the final project of the Mathematics Department students. In order to get the best k-gram value and window size that will be used in the system, a testing process is carried out between document I (100% data) and document II (80% data) by using variations in k-gram values ​​and window sizes. The test results show that the best k-gram ​​and window size are 12 and 4.